Season of conception and risk of hypertensive disorder during pregnancy - Yanxia Xie; Yi Mu; Peiran Chen; Yanping Wang; Xiaohong Li; Li Dai; Zheng Liu; Qi Li; Mingrong Li; Juan Liang; Jun Zhu (BMC Pregnancy and Childbirth)
Abstract Background Hypertensive Disorder during Pregnancy (HDP) is the most prevalent obstetric conditions in maternal health, but the etiology of most cases remains unexplained. Seasonal variations in the conception of HDP may offer insights into the potential seasonal-specific risk factors. Methods Data were sourced from the China’s National Maternal Near Miss Surveillance System (NMNMSS) between January 1, 2012, and December 31, 2021. HDP status was ascertained from the diagnostic records over 400 medical institutions. The conception date was estimated based on the delivery date and duration of gestation length, and the season of conception, were categorised as winter (December to February), spring (March to May), summer (June to August), and fall (September to November). Odd ratios were calculated separately using the logistic regression model. Results Among the 14,073,565 pregnant women analysed, 3.98% met the study’s criteria for HDP as defined in the present study. Maternal conception in spring was associated with a 10% increased risk of HDP (aOR, 1.10 [95% CI, 1.08–1.12]) compared with summer conceptions. Elevated risk of HDP was observed for maternal individuals conceiving in February, March, April, May, and June according to analyses conducted for specific months. The associations were slightly stronger in the subgroup of women diagnosed with gestational hypertension and preeclampsia. Significant disparities exist in this association among the diverse Köppen-Geiger climate zones. Conclusion Significant seasonal variations in the risk for HDP were observed across a range of maternal characteristics, HDP subtypes, and climatc zones. These findings imply the necessity of considering seasonally fluctuating environmental factors in the etiological investigation of HDP. Clinical trial number Not applicable.